Analysis of Comorbidity Disease as A Risk Factor COVID-19 Death - Andi Rizaldi Kurniawan Misbah; Zulfitriani Murfat; Rahmawati; Indah Lestari Daeng Kanang (Future Science)
The COVID-19 disease which became a pandemic in early 2020 was caused by SARS-CoV-2 which attacks the human respiratory system. The transmission of COVID-19 that occurs through human-to-human transmission causes a high risk of infection worldwide. A high-risk factor for death from COVID-19 occurs in people who have comorbidities that aggravate symptoms in COVID-19 patients. Although the incidence of this disease is not influenced by age and gender, the fact that most deaths from COVID-19 occur in elderly men. Comorbidities play an important role in the infection process that occurs, presumably due to an increase in the expression of the ACE2 enzyme, and a decrease in the cellular immune system. This literature review aims to determine the role of comorbid disease as a risk factor for COVID-19 death. This paper was prepared using the Literature Review method with a Narrative Review approach. By referring to research results from reputable national and international journals from 2020 to 2021 through the Pubmed, Clinical Key, and Google Scholar databases. Based on the analysis of the Literature Review, it was found that the presence of comorbid diseases increases the risk of infection, exacerbates symptoms, and death in COVID-19 patients. The comorbid disease with the highest mortality rate was found in hypertension, followed by diabetes mellitus, cardiovascular disease, chronic obstructive pulmonary disease (COPD), and cancer. Patients who have more than one co-morbidity have a higher risk of death if they are infected with COVID-19. Comorbid diseases will increase the risk of death in COVID-19 patients.